Deteksi Formalin Menggunakan Surface Plasmon Resonance (SPR) Berbasis Nanopartikel Perak sebagai Pengembangan Awal Teknologi Food Safety - Muhammad Khoirul Anam; Risma Narindra; Thoyibi T; Kamsul Abraha (Department of Physics, Sebelas Maret University, 2016)
The phenomena of surface plasmon resonance (SPR) has been observed. SPR is reflectance curve as a function of incident angle in Kretschmann configuration. Surface plasmon is electromagnetic waves propagation in the interface area between metal and dielectric that can be excited by using attenuated total reflection (ATR) method. The result of experiment explains that the SPR angle on the thin film system of the prism/silver 1 and the prism/silver 2 is (42.8± 0,05)º with the reflectance value 0.32 and 0.44 respectively. On the prism/silver/silver nanoparticle system, it is obtained that SPR angle value is (4,29 ± 0,05) with the reflectance value 0.29 for the silver 1 and 0.31 for the silver 2. After the thin film system is added with 40% of formalin, SPR angle becomes (43,0 ± 0,05)º with the reflectance value 0.44. Then, after the thin film system is added with 100% of formalin, SPR angle becomes (43,2 ± 0,05)ºwith the reflectance value 0.4. The shifting SPR angle shows that SPR have capability as formalin sensor.